Respuesta :
Subtract the second equation from double the first equation:
2x+6y-2x-(-4y)=0
10y=0
Therefore, y=0. Substituting this into the first equation, we see that:
x+3(0)=3
x=3
Therefore, x=3. The solution to this system is x=3, y=0, or (3, 0).
2x+6y-2x-(-4y)=0
10y=0
Therefore, y=0. Substituting this into the first equation, we see that:
x+3(0)=3
x=3
Therefore, x=3. The solution to this system is x=3, y=0, or (3, 0).
so divide the second equation by 2
x-2y=3
the first equation is
x+3y=3
subsitute
3=3 so therefor
x-2y=x+3y
subtract x from both sides
-2y=3y
add 2y to both sides
0=5y
ofviously y=0 so subsitute
x-2y=3
x-(2)0=3
x-0=3
x=3
x=3
y=0
x-2y=3
the first equation is
x+3y=3
subsitute
3=3 so therefor
x-2y=x+3y
subtract x from both sides
-2y=3y
add 2y to both sides
0=5y
ofviously y=0 so subsitute
x-2y=3
x-(2)0=3
x-0=3
x=3
x=3
y=0